2021
DOI: 10.1021/acsami.1c10536
|View full text |Cite
|
Sign up to set email alerts
|

Enabling Continuous and Improved Solar-Driven Atmospheric Water Harvesting with Ti3C2-Incorporated Metal–Organic Framework Monoliths

Abstract: Solar-powered atmospheric water harvest (SAWH) with metal–organic frameworks (MOFs) represents one of the most sustainable, energy-efficient, and low-cost ways to alleviate water shortage stress in arid regions. However, the daily water productivity of previously developed SAWH devices remains low as they are merely allowed to be operated in batch mode and complete one water harvest cycle every day. This inevitably makes it rather challenging to deploy MOF-based SAWH for water production at scales. To overcome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
40
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(44 citation statements)
references
References 42 publications
4
40
0
Order By: Relevance
“…This suggested that the cross-linked SA network rendered a limited effect on the porosity of Al-Fum, well matching previous reports. 18,28 In comparison to the well isolated pristine Al-fum crystals (Figure S2), scanning electron microscopy (SEM) observations on the cross section of CAS-3 clearly revealed that Al-fum crystals were well accommodated in the cross-linked SA polymer network (Figure 2d). This was further supported by the elemental mapping analysis where the Al element from Al-Fum and the Ca element from the crosslinked SA network were clearly visualized in CAS-3 (Figure 2e).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This suggested that the cross-linked SA network rendered a limited effect on the porosity of Al-Fum, well matching previous reports. 18,28 In comparison to the well isolated pristine Al-fum crystals (Figure S2), scanning electron microscopy (SEM) observations on the cross section of CAS-3 clearly revealed that Al-fum crystals were well accommodated in the cross-linked SA polymer network (Figure 2d). This was further supported by the elemental mapping analysis where the Al element from Al-Fum and the Ca element from the crosslinked SA network were clearly visualized in CAS-3 (Figure 2e).…”
Section: Resultsmentioning
confidence: 99%
“…19,20 Although our recently designed AWH devices enabled us to continuously produce water through multiple WHCs during the daytime, the operation of such a device still heavily depended on the availability of sunlight. 28 This inevitably limited the scaling up of water productivity of the devices with solar heating-driven AWH technology.…”
Section: Introductionmentioning
confidence: 99%
“…One of the adjacent lattice fringes distance is equal to ≈0.25 nm which corresponds to the (102) plane of the single-layer Ti 3 C 2 , whereas the other one was equal to ≈0.32 nm, which is associated with the (316) plane of UZT. [37] The images of elemental mapping demonstrated that Ti, Zr, C, and O are detected and are densely dispersed in the composite, indicating the successful formation of UZT/CFMX. The distribution of F element is not obvious, demonstrating that the HF etchant has been cleaned up in the composite (Figure 1i-n).…”
Section: Resultsmentioning
confidence: 93%
“…One of the adjacent lattice fringes distance is equal to ≈0.25 nm which corresponds to the (102) plane of the single‐layer Ti 3 C 2 , whereas the other one was equal to ≈0.32 nm, which is associated with the (316) plane of UZT. [ 37 ]…”
Section: Resultsmentioning
confidence: 99%
“…The majority of these introduced batch water generation. 28,[69][70][71][72] Recently only one conceptual truly continuously operated prototype has been tested under laboratory conditions using artificial light. 20 The first step towards continuous AWH was to achieve multiple sorptiondesorption cycles in batches.…”
Section: Possible Advancements In System Designsmentioning
confidence: 99%